2002
DOI: 10.1063/1.1497683
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the A 2Π–X 2Π electronic transition in HCCS

Abstract: Articles you may be interested inAccurate ab initio ro-vibronic spectroscopy of the X ̃ 2 Π CCN radical using explicitly correlated methods An ab initio study of the vibronic, spin-orbit, and magnetic hyperfine structure in the X Π 2 electronic state of NCO An ab initio study of the hyperfine structure in the X 2 Π electronic state of CCCH Ab initio study of the vibronic and spin-orbit structure in the X 2 Π electronic state of CCCH Potential energy surfaces for the electronic states of the HCCS radical correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…The most thorough and detailed theoretical studies of the electronic states of HCCS are reported in two recent papers by Perić et al 18,19 For the ground state they obtained 18,20 4 ϭ579 cm Ϫ1 , ⑀ 4 ϭϪ0.329, 5 ϭ374 cm Ϫ1 , ⑀ 5 ϭϩ0.133, ⑀ 45 ϭ0.062, and AϭϪ261 cm Ϫ1 , in excellent accord with the previous microwave values. The authors gave very useful tabulations of the predicted ground state vibronic energy levels for both HCCS and DCCS.…”
Section: Introductionsupporting
confidence: 74%
“…The most thorough and detailed theoretical studies of the electronic states of HCCS are reported in two recent papers by Perić et al 18,19 For the ground state they obtained 18,20 4 ϭ579 cm Ϫ1 , ⑀ 4 ϭϪ0.329, 5 ϭ374 cm Ϫ1 , ⑀ 5 ϭϩ0.133, ⑀ 45 ϭ0.062, and AϭϪ261 cm Ϫ1 , in excellent accord with the previous microwave values. The authors gave very useful tabulations of the predicted ground state vibronic energy levels for both HCCS and DCCS.…”
Section: Introductionsupporting
confidence: 74%
“…9,10,15 The situation is thus analogous to that for the A 2 ⌸ state of HCCS, where we did not find a minimum at nonlinear geometries, but a comparison of the ab initio computed vibronic spectrum with the corresponding findings lead us to the conclusion that it probably exists. 21 At C-CCH bending the ordering of the states is opposite, with the AЈ component placed above the AЉ state. In the same figure the mean potentials and half the difference between the adiabatic potential curves are displayed.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it is analogous to the species like HCCO and HCCS, which have been the subject of recent ab initio investigations carried out in our laboratory. [19][20][21] Encouraged by the results of these studies, which offered a reliable explanation of some intriguing features of the corresponding experimental findings, we try in the present work to solve the controversies concerning the vibronic spectrum of CCCH. The paper is organized as follows: In Sec.…”
Section: Introductionmentioning
confidence: 94%
“…Using the second expression in Eqs. (9) and (11) we obtain for the energy difference of adiabatic potentials where c / 2 À / 1 . The transformation (5) can be comprehended as consisting of two steps.…”
Section: Model Hamiltonian For Handling the Rt Effect In P Electronicmentioning
confidence: 99%
“…[e 1 = e 2 = 0.00695, e 12 = À0.00795 recall that the e-parameters are assumed to be of dimension energy · radian À2 and thus have another numerical values than in the original references] [6,7]; the X 2 P u state of B 2 H þ 2 with e 1 = e 2 = À0.0075, e 12 = 0.0125 (case 5) [8]; the A 2 P state of HCCS (e 1 = À0.0065, e 2 = À0.010, e 12 = À0.0003, case 12) [9]; the X 2 P state of HCCC (e 1 = À0.0350, e 2 = 0.0190, e 12 = 0.00285, case 4) [10]. The X 2 P state of HCCS will be considered explicitly in Section 4.…”
Section: Case (C)mentioning
confidence: 99%